The Effectiveness of Elektronic Hearings on Civil Case Proceedings at the Tanjung Karang District Court - Risky Widodo, Risky Widodo; Nadia Resky, Nadia Resky; Eka Antonia Saputri, Eka Antonia Saputri; Sri Zanariyah, Sri Zanariyah (Dinasti Research, 2026)
The implementation of electronic trials in civil cases is part of the judicial modernization agenda that aims to realize the principles of simple, fast, and low-cost justice. This study analyzes the effectiveness of electronic trials on civil case proceedings at the Tanjung Karang District Court from the perspective of civil procedural law. The research method used is normative-empirical legal research with a legislative, conceptual, and case approach. Data was obtained through literature study and field research in the form of interviews and observations of electronic trial practices. The results of the study show that the implementation of e-court and e-litigation at the Tanjung Karang District Court has normatively supported the realization of case administration efficiency, particularly at the registration and response stages. However, this effectiveness is not yet fully uniform, especially in terms of access to justice for those seeking justice who have limited digital literacy and are not accompanied by legal counsel. In addition, the evidence stage remains a crucial issue due to doubts about the authenticity and strength of electronic evidence, which in practice often requires verification of physical documents. This study concludes that the effectiveness of electronic trials is not only determined by the availability of regulations and technology, but also by the readiness of human resources, the legal culture of society, and the active role of judges in maintaining procedural justice. Therefore, strengthening digital literacy, legal assistance, and improving the legal framework for evidence are important prerequisites for optimizing electronic trials in civil cases